Study of the evolution of Cu-Cu bonding interface imperfection under direct current stressing for three dimensional integrated circuits - Made, Riko I. (2012)
While the ultimate goal of Cu interconnection in 3D-IC is to have Cu as both the glue layer and interconnection line, there has been numerous demonstration of Cu-Cu bonding that shows the bonding interface is not always perfect. This work investigates the evolution of Cu-Cu bond interface under prolonged current stress by combining electrical current stressing and bond interface cross-sectional analysis. Voids at the bond interface were observed to be driven by electromigration to the adjoining interconnect line, leading to early failures of the line. This may have significant impact on the future of 3D-IC technology that utilizes Cu-Cu bonding, and it may be mitigated by inserting a barrier layer in between the bond interface and the interconnect line.